A meta-scientific broad panorama of ethical aspects in the Brazilian IHC - Carvalho, Luiz Paulo (2022)
Ethics is a field of study that analyses practices, their principles, customs, and habits. The Grand Research Challenges in Human-Computer Interaction in Brazil (GranDIHC-BR) between 2012 and 2022 highlighted the relevance of the topic Ethics in the context of Human Values. Aligned with that, we claim that computational techniques are not neutral and, therefore, ethical analysis is essential to the design of applications as well as theoretical or conceptual research. The goal of this work is to provide an understanding on how researchers have addressed the ethical aspects by analyzing the publications of the IHC-BR: the Brazilian Symposium on Human Factors in Computing Systems, the leading conference dedicated to HCI in Brazil. Thus, we conducted a Systematic Literature Review guided by the main research question: how does ethics permeate research published between 2006 and 2021? As a result, although less than 5% of the papers discussed ethical content, we observed a significant growth in ethical aspects over the years, both associated with the meta-research and its application.